Sharia Cooperative Institutional Development: The Block Chain Approach (Case Study in Bulak, Surabaya City) - Masroro Lilik Ekowanti; Aniek Sulestiani; Wildan Taufik Raharja (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2020)
A community-based institutional building of syariah cooperatives requires information and communication technology. This has led to a block chain approach that benefit from the industrial revolution 4.0. The institutional concept that was developed 60 years ago by JE. Eaton (1972) is very relevant in this context. In this study, we employ a qualitative method with descriptive research. Our findings shows that community response to knowledge and awareness for adopting syariah cooperative is satisfactorily good as indicated by the establishment of a syariah pra-cooperative named "Nurus Shobah" in 2019. The output performance is effective : the number of members increased up to 34%, while the quality of sirkah is 98%. Hampering factors are delayed adoption of block chain approach due to lack of exposition to members, underperforming of software, and administration is still manually carried out. A supportive factor exists in which functionally, the cooperative has been partnering with neighbouring university through a supervision program. We therefore conclude that the institutional building of syariah cooperative in Bulak, Surabaya has not been fully implemented. A block chain approach is to be soon adopted to support the cooperative